VERIFICATION OF HYBRID NUMERICAL SCHEME FOR THE CASE OF COMPRESSIBLE JET IMPINGIMENT ON FLAT PLATE - M. V. Kraposhin; S. V. Strijhak (Научный вестник МГТУ ГА)
The article deals with the questions of mathematical modeling of compressible jet outflow from model nozzle and jet impingiment on flat plate at various values of n. pisoCentralFoam solver which is based on the Kurganov-Tadmor hybrid numerical scheme, PISO algorithm and finite volume method, is used for the solution of this problem. The model, based on unsteady Reynolds equation and K-omega SST turbulence model with boundary functions is used for compressible jet calculation. The problem definition for calculation of jet impingiment on flat plate is given. The simulation domainwas selected as a rectangle. Only a half of the nozzle was considered for simplification. The mixed boundary condition for pressure setting in case of free jet was used on the outlet of simulation domain. The special condition for the pressure with table data, allowed to increase the value of pressure gradually, was used on the inlet of simulation domain. The value of the jet pressure degree was selected as n = 2.5 and n = 5.0. The results of distribution of the velocity magnitude, field pressure, upon symmetry axes were received. The simulations were done with grids 100 000-500 000 cells. The average value of y+ was equal to 270. The calculations were done for the end time Tend = 0.01 s. Comparison of the results of pressure distribution calculation based on nozzle length on different grids with the results of the experiment is carried out. The coincidence to engineering accuracy of 5 % is received.